Average intensity and spreading of a radially polarized multi-Gaussian Schell-model beam in anisotropic turbulence. (October 2018) - Cheng, Mingjian; Guo, Lixin; Li, Jiangting; Yan, Xu; Dong, Kangjun; You, Yang
Highlights: Propagation of radially polarized multi-Gaussian Schell-model (MGSM) beams in the turbulence is studied. The robustness of radially polarized MGSM beams in the turbulence is subject to beam order. Turbulence-induced spreading is suppressed with the enhanced anisotropy coefficient. Abstract: Analytical expressions of average intensity and long-term beam width for a radially polarized multi-Gaussian Schell-model (MGSM) beam in anisotropic atmospheric turbulence are developed based on the extended Huygens-Fresnel principle. The influences of anisotropic non-Kolmogorov turbulence and source parameters on the average intensity, polarization and long-term beam spreading of radially polarized MGSM beam are examined in detail. The source correlations, free-space diffraction and turbulent effect jointly affect both the intensity and polarization profiles of the beam propagated in the atmosphere. As a radially polarized MGSM beam propagates in the atmosphere, increasing the associated beam order can lower the evolution rate from its flat-topped beam profile into a Gaussian beam profile because of the turbulent effect. Variations in the average intensity and long-term beam width are closely related to the propagation distance, power spectrum index, inner-scale, initial spatial coherence, and beam width. The atmospheric turbulence-induced beam spreading is generally suppressed with the enhanced anisotropy coefficient.